Oracle SQL*Plus : the definitive guide - Gennick, Jonathan (O'Reilly, 1999)
This book is the definitive guide to SQL*Plus. If you want to take best advantage of the power and flexibility of this popular Oracle tool, you need this book. SQL*Plus is an interactive query tool that is ubiquitous in the Oracle world. It is present in every Oracle installation and is available to almost every Oracle developer and database administrator. SQL*Plus has been shipped with Oracle since at least version 6. It continues to be supported and enhanced with each new version of Oracle, including Oracle8 and Oracle8i. It is still the only widely available tool for writing SQL scripts. Despite this wide availability and usage, few developers and DBAs know how powerful SQL*Plus really is. This book introduces SQL*Plus, includes a quick reference to all of its syntax options, and, most important, provides chapters that describe, in step-by-step fashion, how to perform all of the tasks that Oracle developers and DBAs want to perform with SQL*Plus -- and maybe some they didn't realize they COULD perform with SQL*Plus. You will learn how to write and execute script files, generate ad hoc reports, extract data from the database, query the data dictionary tables, customize your SQL*Plus environment, and use the SQL*Plus administrative features (new in Oracle8i). This book is an indispensable resource for readers who are new to SQL*Plus, a task-oriented learning tool for those who are already using it, and a quick reference for every user. A table of contents follows: Preface Introduction to SQL*Plus Interacting with SQL*Plus Generating Reports with SQL*Plus Writing SQL*Plus Scripts Extracting Data with SQL*Plus Exploring Your Database with SQL*Plus Advanced Scripting Tuning and Timing The Product User Profile Administration with SQL*Plus Customizing Your SQL*Plus Environment A. SQL*Plus Command Reference B. Connect Strings and the SQL*Plus Command Appendices. -- provided by publisher.